(untitled) (AYUSHDHARA, 2023)
What is good for health and what is to be avoided is very important to stay healthy and this acceptance and rejection is depends on our own constitution i.e., Dehaprakruti as the Prakruti of the individual is unique. Netra is supreme Dhyanendriya among all the five and it is very important as we acquired all the knowledge primarily through Netra. Hypertensive retinopathy is the retinal vascular damage caused by hypertension. Prompt and accurate diagnosis of hypertensive retinopathy, especially when associated with malignant hypertension is necessary to avoid visual loss and systemic morbidity. Knowing owns constitution enables us to understand the function of one’s entire life and dictates the form of the body and also it contains one’s balance point as well as one’s tendencies towards disease. This study will be helpful to deal with patients of hypertensive retinopathy and also to overcome its complications by giving appropriate patients education regarding proper Ahar, Vihar, Dinacharya and Ritucharya according to Dehaprakruti. So we undertaken the study entitled as “An observational study to validate the relationship between hypertensive retinopathy and Dehaprakruti.” In the study already diagnosed 90 patients of Hypertensive retinopathy as per inclusion and exclusion criteria of age group 40-70 yrs were taken. Prakruti Parikshan of the patients done with the help of questioner’s. In the study maximum 95.55% patients had essential hypertension. It was observed that maximum 64.44% patients were of Vatapitta Dehaprakruti followed by 22.22% that of Vatakapha Dehaprakruti but no any significant association was found in between grades of hypertensive retinopathy and Dehaprakruti. It was also found that visual impairment occurred in maximum 68.89% patients out of which maximum 45 patients were of Vatapitta Dehaprakruti and significant association was found between hypertensive retinopathy and Dehaprakruti.